Integrated Partnership and Quality Management at State Vocational High Schools (Multi-Site Study at SMKN 3 Palangka Raya and SMKN 4 Banjarmasin) - Setiawan, Nopri; Sandan, Maria Fransisca; Aslamiah, Aslamiah; Cinantya, Celia (Riwayat: Educational Journal of History and Humanities, 2024)
This study investigates the integrated management of partnerships and quality assurance in Vocational High Schools (SMK), focusing on a multi-site comparison between SMKN 3 Palangka Raya and SMKN 4 Banjarmasin. Utilizing a qualitative methodology with a multi-site case study approach, the research examines how these schools collaborate with industry partners to enhance educational quality and improve the employability of graduates. Key themes identified include the frequency of industry collaboration, curriculum flexibility, and the regularity of quality assurance evaluations. The findings suggest that SMKN 4 Banjarmasin, with more frequent industry engagements and comprehensive quality evaluations, achieves better outcomes in terms of graduate employment compared to SMKN 3 Palangka Raya. This underscores the critical role of integrated partnership and quality management in aligning vocational education with labor market needs. The study highlights the importance of continuous industry involvement and adaptive curriculum management as essential strategies for enhancing the effectiveness of vocational education. The results offer valuable insights for policymakers and vocational school administrators, proposing that a well-coordinated approach to partnership and quality assurance can significantly improve the relevance and outcomes of vocational education programs. This research contributes to the broader discourse on the management of vocational schools, particularly in addressing regional differences in partnership management practices.